Legal Certainty for Holders of Land Documents Other Than Certificates in Relation to Electronic Land Certificates - Parmashta Kristiawan, Sarah (Journal Research of Social Science, Economics, and Management, 2025)
In the era of globalization and digitalization, land registration in Indonesia has undergone significant transformation through the implementation of electronic certificates. This research aims to examine the legal certainty for holders of land documents other than certificates in relation to electronic land certificates under the Regulation of the Minister of ATR/BPN Number 3 of 2023. The research method used is normative juridical, focusing on the analysis of legislation and jurisprudence. The results indicate that although electronic certificates provide security guarantees and ease of access, land rights holders using traditional documents like Letter C, Girik, and Petuk D still face challenges regarding legal certainty. Failure to register land within the specified timeframe may result in these documents not being recognized as valid proof of ownership. Therefore, communities still using conventional documents are urged to promptly register and convert these documents into Certificate of Ownership (SHM) to obtain stronger legal protection. This research also recommends enhancing socialization and literacy regarding the importance of land ownership documents in the form of certificates. In this regard, electronic certificates can facilitate the land registration process to support legitimate ownership and reduce disputes in the land sector.